Exploring assessment of spoken language processing in spoken language processing disorder - Sone, Piyush; Kale, Apoorva; Mohan, Maneesha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Spoken language processing model by Medwetsky in the year 2011, provides an overview of auditory, cognitive and language mechanisms engaged in the processing of spoken language. It shows how deficits in the various stages of processing can be manifested and provides a framework of developing an effective interdisciplinary test battery. Present case study was designed to provide a novel way of assessment for children with spoken language processing disorders. An 8 years old Marathi speaking child who showed difficulty in following the instructions and poor attention was evaluated with spoken language processing test battery. The child was found to have deficits in various levels of spoken language processing. This holistic assessment will help to know a case in a better way and domain specific intervention of spoken language processing disorder. Spoken language processing disorder occur when a breakdown in any of these mechanisms impacts an individual’s ability to effectively process and use information that is heard. We recommend that domain specific holistic assessment is essential in spoken language processing disorder. Spoken language test battery can be used for comprehensive assessment of all processes involved in the spoken language processing model.